2015 Transducers - 2015 18th International Conference on Solid-State Sensors, Actuators and Microsystems (TRANSDUCERS) 2015
DOI: 10.1109/transducers.2015.7181145
|View full text |Cite
|
Sign up to set email alerts
|

Flow compensation in a MEMS dual-thermal conductivity detector for hydrogen sensing in natural gas

Abstract: Conventional thermal conductivity detectors (TCDs) demonstrate a flow dependence. The approach presented here to reduce the flow dependence is based on the on-line flow compensation using two thin-film sensors on membranes in parallel on the same chip that are differentially operated. These are laterally identically, but with a different depth of the detection chamber, resulting in different quasi-static sensitivities to the thermal conductivity of the sample gas. The effects of conduction and convection in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Over the last few decades, the semiconductor industry has experienced exponential growth. Semiconductors are widely used in different sensing applications ranging from surveillance to medical devices, as well as environmental applications and beyond [1][2][3][4][5]. One of the most important results of this industry is the CMOS image sensor (CIS) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, the semiconductor industry has experienced exponential growth. Semiconductors are widely used in different sensing applications ranging from surveillance to medical devices, as well as environmental applications and beyond [1][2][3][4][5]. One of the most important results of this industry is the CMOS image sensor (CIS) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…de Graaf et al suggested a deep and shallow groove design, which can compensate for the flow rate impaction effectively [25,26]. Whereas the thermal conductivity sensitivity is decreased due to offsetting the deep groove's output.…”
Section: Introductionmentioning
confidence: 99%